Proposed Pathway for Nigerian Libraries in The Face of Prevailing Educational and Societal Requirements - Onuoha, Juliet; David-West, Boma Torukwein; Chukwueke, Chukwuemeka (Ghana Library Journal, 2023)
It is very clear that the library, regardless of the type, plays a fundamental role in the educational and societal development of any nation. The resources and services offered by these libraries create opportunities for learning, support literacy and education, and help shape the new ideas and perspectives that are central to a creative and innovative society. Sadly, most of these libraries Nigeria are highly faced with great challenges, hence, the need to device a pathway. This paper critically looked at the state of the Nigerian libraries in terms of its educational and societal requirements. However, before delving into the pathway for the Nigerians libraries in the face of prevailing educational and societal requirements, some of the challenges faced by these libraries were x-rayed. The paper concludes that much is expected of these Nigerian libraries which have strived from the periods of less competition to the period of high competition and expectation. in order to meet these numerous educational and societal requirements, there is need for a pathway, especially a joint role to be played by the librarians, educators, and government. One of which is the issue of a national policy and proper funding of these libraries.